A quest for humanity : the good society in a global world - Boldt, Menno (University of Toronto Press, 2011)
"In A Quest for Humanity, Menno Boldt presents a persuasive new framework for achieving a human social order in the global age. Boldt explores the concept of 'the good society' as a world in which every person can realize their potential for humanity through liberty, social justice, and equal human dignity. A Quest for Humanity innovatively positions globalization as a deterministic phenomenon of expanding interdependence and shared knowledge, resulting in ever-larger economic and political jurisdictions, but also creating social and psychological links between peoples across the world. Boldt challenges mainstream certainty that Western democracy and constitutional human rights are the exemplary doctrines for the global good society. With a fresh vision designed to inspire a universal acknowledgement of human dignity, A Quest for Humanity powerfully affirms the value of each human being."--